The human skeleton in forensic medicine - Krogman, Wilton Marion, 1903-1987; İşcan, M. Yaşar; Steyn, Maryna (Springfield, Illinois Charles C Thomas, 2013)
This classic in forensic anthropology has been thoroughly updated and greatly expanded for the new Third Edition. The result presents the state of the medicolegal art of investigating human skeletal remains. The third edition follows more than 25 years after the second edition. During this time, considerable changes occurred in the field and Forensic Anthropology became a distinct specialty in its own right. Included in the book are detailed discussions on crime scene investigation, including excavation techniques, time interval since death, human or animal remains, mass graves, and preparation of remains. Existing chapters, all dramatically revised, bring readers in line with the current concepts of skeletal age; determination of sex; assessment of ancestry; calculation of stature; factors of individualization; superimposition and restoration of physiognomy. There is also a section on dental analysis examining such topics as dental anatomy, nomenclature, estimation of age in subadults and adults, determination of sex and ancestry, and pathological conditions. New additions are chapters on skeletal pathology and trauma assessment. A new chapter has also been added on “Forensic Anthropology of the Living.” Although all of the sections of the book have been updated significantly, the authors have retained some sense of history to recognize the many pioneers that have shaped the discipline. The text will assist forensic anthropologists and forensic pathologists who have to analyze skeletons found in forensic contexts. This book has a global perspective in order to make it usable to practitioners across the world. Where possible, short case studies have been added to illustrate the diverse aspects of the work.
Keywords: Medicina legal; Antropología física; Libros electrónicos